2015
DOI: 10.1074/jbc.m115.686873
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α6β4 Promotes Autocrine Epidermal Growth Factor Receptor (EGFR) Signaling to Stimulate Migration and Invasion toward Hepatocyte Growth Factor (HGF)

Abstract: Background: Integrin ␣6␤4 is overexpressed in pancreatic cancer and enhances invasion. Results: Integrin ␣6␤4 coordinately up-regulates AREG, EREG, and MMP1 through DNA demethylation and NFAT5 that in turn enhances HGF-mediated invasion. Conclusion: Integrin ␣6␤4 stimulates HGF-dependent invasion through autocrine EGFR signaling. Significance: HGF-stimulated invasion is dependent on autocrine EGFR signaling, thus implicating why EGFR inhibitors are effective in a complex tumor microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
4
26
0
Order By: Relevance
“…These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with previous studies demonstrating the association of TMEM16A expression with the EGFR signaling pathway in breast cancer and HNSCC (11,12,22). Given that the EGFR signaling pathway in pancreatic cancer relies on the EGFR ligands (13,14) and promotes pancreatic ductal adenocarcinoma (PDAC) development by regulating acinar-ductal metaplasia, cancer cell migration, and the occurrence of metastasis (15,17,18,23), our finding suggests that TMEM16A could play an essential role in ligand-induced EGFR signaling pathway in pancreatic cancer.…”
Section: Tmem16a Is Overexpressed In Pancreatic Ductal Adenocarcinomasupporting
confidence: 93%
“…In pancreatic cancer, the EGFR signaling pathway is involved in both cancer initiation and the development of metastasis (13,14). Unlike breast cancer and HNSCC that are associated with mutations rendering EGFR constitutively active, pancreatic cancer involves activation of the EGFR signaling pathway by extracellular ligands such as EGF, TGF-α, or Epiregulin (15)(16)(17)(18). It is therefore important to determine whether TMEM16A regulates EGFR signaling in pancreatic cancer cells in a manner that depends on ligand activation of EGFR.…”
mentioning
confidence: 99%
“…In particular, integrin β4 has been shown to interact with EGFR in lipid rafts where it enhances cell growth and proliferation [34]. Furthermore, our lab has demonstrated that in pancreatic carcinoma cells, integrin α6β4 promotes autocrine EGFR signaling [35]. …”
Section: Discussionmentioning
confidence: 99%
“…Activation of EGFR would activate variable signaling pathways after its activation such as PI3-kinase-, Rac1-and MAPK-dependent pathways by coupling ErbB2 receptor [44], which have the stimulatory or inhibitory action on the ENaC-mediated Na + transport. Further, the EGFR stimulation connects with hepatocyte growth factor [51]. The substrate of hepatocyte growth factorregulated tyrosine substance (Hrs) is involved in the endosomal membrane trafficking [52], and Hrs binds ENaC controlling the intracellular ENaC trafficking [53].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%